Unjuk Kerja Model-Model Kincir Angin Savonius Dua Tingkat Dengan Kelengkungan Sudu Termodifikasi - Ir. Rines (Media Teknika, 2016)
Savonius windmill is a kind of vertical axis windmill which is potential used to capture the energy from the wind. This researchs objective is to investigate about the dimension effects on the performance of the Savonius windmill models with modified curves and blades configuration. All of the models were made in two stages which each stage have two blades. Six dimension variations of windmill models has been made and investigated in range from 0.432 m2 to 0.552 m2. This research was conducted in a wind tunnel at wind speed range between 4 m/s to 7 m/s. The results showed that there were effects of the dimension of windmill on its performance. The lowest value of peak power coefficient is produced by a windmill model 92 cm of rotor,s diameter and 60 cm in height, that is about 0.31 at tip speed ratio 1.08. The highest one is produced by windmill model 60 cm of rotor,s diameter and 92 cm in height, that is about 0.49 at tip speed ratio 1.18.